Selective Modification for Red‐Shifted Excitability: A Small Change in Structure, a Huge Change in Photochemistry - Becker, Yvonne (Chemistry, 2020)
We developed three bathochromic, green‐light activatable, photolabile protecting groups based on a nitrodibenzofuran (NDBF) core with D‐π‐A push–pull structures. Variation of donor substituents (D) at the favored ring position enabled us to observe their impact on the photolysis quantum yields. Comparing our new azetidinyl‐NDBF (Az‐NDBF) photolabile protecting group with our earlier published DMA‐NDBF, we obtained insight into its excitation‐specific photochemistry. While the “two‐photon‐only” cage DMA‐NDBF was inert against one‐photon excitation (1PE) in the visible spectral range, we were able to efficiently release glutamic acid from azetidinyl‐NDBF with irradiation at 420 and 530 nm. Thus, a minimal change (a cyclization adding only one carbon atom) resulted in a drastically changed photochemical behavior, which enables photolysis in the green part of the spectrum.